ROLE OF DIDACTIC GAMES IN SCIENCE TEACHING (European Journal of Interdisciplinary Research and Development, 2024)
Today, almost all developed countries recognize that the student is the central figure of the lesson in the educational process. All other actions revolve around it. In fact, we turn to modern methods of teaching to achieve the goal of education based on new social and economic requirements. Different non-traditional methods are used in the teaching of mother tongue and literary subjects. Among them, didactic games serve to discover important aspects of the student as a person, both psychologically and intellectually. Let's talk about the word "Didactics" here. Didactics (Greek "didaktikos" - teacher, educator) is a branch of pedagogy. The term didactics was first used in Europe in the 17th century by scientists who wrote works about the teaching and learning process. The goal of didactics today is to find the most effective methods and ways of teaching.